INTELLIGENT CONTROL SYSTEM OF CHEMICAL-TECHNOLOGICAL PROCESSES OF STRUCTURING OF MULTICOMPONENT ELASTOMER COMPOSITES BASED ON THE PRODUCTION MODEL - A. S. Kuznetsov; V. F. Kornushko (Тонкие химические технологии)
A systemic analysis of the life cycle of products from elastomeric materials was carried out. The main modules of a management system for managing the life cycle - development, production and distribution of products from elastomeric composites on the basis of the integrated information system are described. The main control points of the process control are indicated. A detailed description of complex chemical-technological processes of multicomponent elastomeric composites structuring from the positions of a system approach based on a complex of information and production models is proposed. The model of an automated control system for the chemicaltechnological processes of elastomeric composites structuring based on vibration-rheometric data is considered, which is an example of the use of a control system based on indirect indicators. It is shown that the disturbing effects leading to the deviation of the process indices from the given ones are of a prescription and technological nature. The architecture of the integrated information management system for complex chemical-technological processes of multicomponent elastomeric composites mixing and structuring based on the production rules system is proposed. A block diagram of the algorithm for processing the main rheometric information of elastomeric composites structuring is given.